Pendampingan Penyusunan Modul Ajar Kurikulum Merdeka - Ahmad Nurhuda; Safri Mardison; Tegar Muhammad Iqbal (Tarikhuna: Journal of History and History Education, 2023)
The implementation of the Merdeka Curriculum in madrasahs still faces challenges, particularly regarding the readiness of teachers in developing teaching modules. This community service activity aims to improve the understanding and skills of MTs social studies teachers in West Pasaman Regency in developing contextual Merdeka Curriculum teaching modules. The activity was carried out using a Community-Based Research (CBR) approach through situation analysis, training, mentoring, and reflection with Focus Group Discussions (FGD). The results of the activity showed that MTs social studies teachers were able to develop 7th grade social studies teaching modules in accordance with the requirements of the Merdeka Curriculum, apply differentiated learning, and integrate the Rahmatan Lil Al Alamin Student Profile. Participant engagement was excellent, and all participants stated that the activity was beneficial. However, further mentoring with more adequate time allocation is needed to refine the teaching modules. This activity was effective in supporting the implementation of the Merdeka Curriculum in madrasahs.